2009
DOI: 10.1126/science.1171477
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Carbon Dioxide Concentration Across the Mid-Pleistocene Transition

Abstract: During the Mid-Pleistocene Transition (MPT; 1,200-800 kya), Earth's orbitally paced ice age cycles intensified, lengthened from ∼40,000 (∼40 ky) to ∼100 ky, and became distinctly asymmetrical. Testing hypotheses that implicate changing atmospheric CO 2 levels as a driver of the MPT has proven difficult with available observations. Here, we use orbitally resolved, boron isotope CO 2 data to show that the glacial to interglacial CO 2 difference increased from ∼43 to ∼75 μatm across the MPT, mainly because of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
424
2
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(468 citation statements)
references
References 27 publications
38
424
2
4
Order By: Relevance
“…5 reconstructions do not show a long-term decline during the Pleistocene, but suggest that glacial values prior to ~1 Ma were 30±30 atm higher than the late Pleistocene (Hönisch et al, 2009). In contrast, estimated interglacial pCO 2 values before the MPT are statistically the same as those of the late Pleistocene, with a temporary reduction in interglacial pCO 2 between 1 and 0.6 Ma (Hönisch et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 72%
“…5 reconstructions do not show a long-term decline during the Pleistocene, but suggest that glacial values prior to ~1 Ma were 30±30 atm higher than the late Pleistocene (Hönisch et al, 2009). In contrast, estimated interglacial pCO 2 values before the MPT are statistically the same as those of the late Pleistocene, with a temporary reduction in interglacial pCO 2 between 1 and 0.6 Ma (Hönisch et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 72%
“…2009) but will likely experience a doubling of CO 2 in the next 80 years. This is a short period for evolutionary change especially given the rapid rise from 280 ppm to current ~400 ppm CO 2 since the start of the industrial revolution.…”
Section: Discussionmentioning
confidence: 99%
“…At an evolutionary timescale, the variation in CO 2 has been even larger, ranging from 3000 ppm in the Devonian down to 180 ppm during the Pleistocene Ice Age (Royer 2006; Hönisch et al. 2009). It is only after the industrial revolution that CO 2 levels started to rise from 280 ppm to the 400 ppm we have today.…”
Section: Introductionmentioning
confidence: 99%
“…Though the data is sparse it seems to indicate a drop in both the interglacial level of carbon dioxide from ~290 ppm to ~ 260 ppm and the glacial level from 220 ppm to 180 ppm. At the MBE the glacial level remains the same but the interglacial level rises to it pre-EMPT level of 290 ppm (Hönisch et al, 2009). Hence the cooling trend through the EMPT could have been driven by the observed reduced concentration of greenhouse gases in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the critical size of the Northern Hemisphere ice sheets may have been influenced by changing levels of greenhouse gases (Clark et al, 2006;Crowley and Hyde, 2008;DeConto et al, 2008). The atmospheric carbon dioxide reconstruction by Hönisch et al (2009) shows significant changes at the EMPT and the Mid-Brunhes Event (MBE) see Figure 7. Though the data is sparse it seems to indicate a drop in both the interglacial level of carbon dioxide from ~290 ppm to ~ 260 ppm and the glacial level from 220 ppm to 180 ppm.…”
Section: Discussionmentioning
confidence: 99%